Robust increase of leaf size by Arabidopsis thaliana GRF3-like transcription factors under different growth conditions - Beltramino, Matias (2018)
An increase in crop yield is essential to reassure food security to meet the accelerating global demand. Several genetic modifications can increase organ size, which in turn might boost crop yield. Still, only in a few cases their performance has been evaluated under stress conditions. MicroRNA miR396 repress the expression of GROWTH-REGULATING FACTOR (GRF) genes that codes for transcription factors that promote organ growth. Here, we show that both Arabidopsis thaliana At-GRF2 and At-GRF3 genes resistant to miR396 activity (rGRF2 and rGRF3) increased organ size, but only rGRF3 can produce this effect without causing morphological defects. Furthermore, introduction of At-rGRF3 in Brassica oleracea can increase organ size, and when At-rGRF3 homologs from soybean and rice are introduced in Arabidopsis, leaf size is also increased. This suggests that regulation of GRF3 activity by miR396 is important for organ growth in a broad range of species. Plants harboring rGRF3 have larger leaves also under drought stress, a condition that stimulates miR396 accumulation. These plants also showed an increase in the resistance to virulent bacteria, suggesting that the size increment promoted by rGRF3 occurs without an obvious cost on plant defenses. Our findings indicate that rGRF3 can increase plant organ size under both normal and stress conditions and is a valuable tool for biotechnological applications.